An Analysis of Grammatical Errors in Students' Academic Writing Using Grammarly App - Lailatus Saniyah; Fatih Al Fauzi; Imam Ghozali (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2026)
This study investigates the grammatical errors found in the academic writing of fourth-semester students at a university in Jember. Using a descriptive qualitative approach, the research focuses on analyzing errors based on the Surface Strategy Taxonomy by Dulay, Burt, and Krashen, which classifies mistakes into omission, addition, misformation, and misordering. The data were collected from students’ final exam writing and analyzed with the help of the Grammarly application, supported by Corder’s error analysis steps, including collecting data, identification of errors, description of errors, and explanation of errors. Several types of errors were found in this study. Among them are the Omission of (suffix -s, article, preposition, pronoun, and object), Addition of (preposition, verb, article, and suffix), Misformation of (verb, preposition, and conjunction), and less Misordering. Omission errors typically occur due to the lack of the suffix "-s" at the end. Addition errors usually occur due to the addition of articles and suffixes that are not needed, misformation errors due to incorrect verb usage, and Misordering  just errors in 1 sentence. A common issue was students' overgeneralization of grammar rules, especially in verb usage and auxiliary structures. The research findings show that many students have difficulty with basic grammar, especially the use of verbs and subject-verb agreement. This highlights the need for focused instruction and adaptive teaching strategies to address common errors and improve writing skills.